Go Green Go to School: Greening and Conservation of the School Environment as a Love for the Environment Movement - Agung Prasetyo; Mahananto; Suswadi; Norbertus Citra Irawan; Teguh Supriyadi (Universitas Tunas Pembangunan Surakarta, 2023)
Aside from environmental improvement, the importance of socializing greenery in the school environment was planting love for the environment among young people, especially students. The methods used in this community service activity are surveys, counseling, and demonstrations. The implementation of greening socialization activities with teachers and students went smoothly. Students can understand this dedication so that for future programs, the team will carry out programs to increase the clustering of Adiwiyata Green School.